2015
DOI: 10.1007/s12221-015-1294-0
|View full text |Cite
|
Sign up to set email alerts
|

Colorating and mechanical performance of low-density polyethylene (LDPE)/dye-loaded shell powder (DPSP) composites

Abstract: Filling and colorating are two important procedures in the polymer production. In this work, a bio-filler dye-loaded shell powder (DPSP) was prepared at first and then its filling and colorating effects on low density polyethylene (LDPE) polymer were investigated. SEM analysis showed the good dispersion of DPSP and strong interfacial adhesion. Mechanical property studies indicated that the incorporation of DPSP had an excellent filling effect at lower loading rate. Uniform color distribution in the specimens w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The favorable filler dispersion and compatibility resulted in desired stress transfer from the PP matrix to the fillers throughout the external loading, causing increases in the tensile strength, fracture strength, and flexural strength . In addition, a crosslink structure could be formed by the active surface of the filler particles bonding with several macromolecular chains, leading to the further reinforcement. Due to the good interfacial interaction, when subjected to impact forces, the composites were able to withstand some fraction of the load, and furthermore, the flexible hydrocarbon chains adhered to the fillers (Figure ) could change their molecular conformation, which facilitated the absorption of impact energy and the improvement in impact strength.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The favorable filler dispersion and compatibility resulted in desired stress transfer from the PP matrix to the fillers throughout the external loading, causing increases in the tensile strength, fracture strength, and flexural strength . In addition, a crosslink structure could be formed by the active surface of the filler particles bonding with several macromolecular chains, leading to the further reinforcement. Due to the good interfacial interaction, when subjected to impact forces, the composites were able to withstand some fraction of the load, and furthermore, the flexible hydrocarbon chains adhered to the fillers (Figure ) could change their molecular conformation, which facilitated the absorption of impact energy and the improvement in impact strength.…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, as can be seen from the photograph, redness was uniformly distributed in all the DPSP/PP composite specimens, although the filler amount increased to 20 wt %. In this article, PP composites were colored through the incorporation of DPSP and the introduced dye existed in two states in the composites . Part of the dye was loaded on the shell powder surface for organic modification as discussed in section “Mechanical Properties of PP Composites,” while others were desorbed, and evenly dispersed into the polymer matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The bands at 1361.41, 1444.55, and 1582.99 cm −1 were due to bending vibration of CN, aromatic stretching vibrations and NN stretching vibrations, respectively. The peak at 3471.45 cm −1 belonged to the characteristic absorption peak of NH 2 …”
Section: Resultsmentioning
confidence: 99%
“…The size distribution and corresponding cumulative curves of SP and DSP are shown in Figure . It can be seen that compared to that of SP, the size distribution of DSP is more concentrated to small values, which could be ascribed to the second pulverization during DSP preparation . The test results also showed that approximately 25% of SP was less than 0.163 μm in diameter, 50% less than 0.240 μm, 75% less than 0.384 μm, and 90% less than 0.644 μm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation